2020
DOI: 10.15835/nsb12410752
|View full text |Cite
|
Sign up to set email alerts
|

Vegetative propagation of cornelian cherry (Cornus mas L.) selections

Abstract: Cornelian cherry (Cornus mas L) is one of the most valuable fruit shrubs of the Cornaceae family, and therefore the vegetative propagation of the valuable selections is necessary because the material obtained must be used for the future. 4 genotypes were studied (2 perspective selections: H1 and H3 and two cultivars used as a control: ‘De Bucovăț’ (B) and ‘De Orhei’ (O) and propagated by grafting (the grafting method used was improved copulation. Biometric observations were focused on diameter below the point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Finally, asexual propagation through grafting has been attempted on European C. mas germplasm with positive results [ 54 ], showing that successful grafting in C. mas can enhance growth and development of the scion [ 55 ]. For the Greek native C. mas genotypes studied herein, the method of grafting a genotype with high phytochemical potential but low rooting capacity onto another genotype with improved rooting capacity may provide a good option in dealing with difficult-to-root genotypes but with valuable fruit traits.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, asexual propagation through grafting has been attempted on European C. mas germplasm with positive results [ 54 ], showing that successful grafting in C. mas can enhance growth and development of the scion [ 55 ]. For the Greek native C. mas genotypes studied herein, the method of grafting a genotype with high phytochemical potential but low rooting capacity onto another genotype with improved rooting capacity may provide a good option in dealing with difficult-to-root genotypes but with valuable fruit traits.…”
Section: Discussionmentioning
confidence: 99%
“…[13,52]. A potential strategy that has been employed in other species to overcome the genotype problem in asexual propagation has been the method of grafting a desirable hard-to-root genotype onto a genotype with high rooting capacity for the steadfast production of stock material [53][54][55]. However, further research is suggested on the asexual propagation of the A. ovalis germplasm studied herein, including an assessment of grafting methods based on more extensive propagation data.…”
Section: Asexual Propagation Of Greek Native Amelanchier Ovalismentioning
confidence: 99%